Unravelling features in post COVID mucormycosis: case series with review of literature - Amaran, E. G. Yog Naag; Puranik, Surekha R.; Puranik, Rudrayya S.; Ramdurg, Praveenkumar; Srinivas, Naveen; Ramesh, Saahil (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
In the midst of the severe acute respiratory syndrome coronavirus 2 (SARS COV-2) pandemic, the victims are acquiring secondary infections like mucormycosis. Rhinocerebral mucormycosis (ROCM), is the most prevalent form and is an invasive, opportunistic fungal infection that typically affects immunocompromised patients. It exhibits a pronounced propensity to invade blood arteries, resulting in tissue thrombosis, necrosis, and infarction. Early conventional and advanced medical imaging like computed tomography (CT) and magnetic resonance imaging (MRI) is helpful in assessing the extent of involvement of this lethal disease which requires prompt and aggressive treatment. Despite of aggressive therapy, which includes disfiguring surgical debridement and frequently adjunctive toxic antifungal therapy, the overall mortality rate is high. The prime objective of present study focuses upon, unravelling the aberrant imaging presentations along with the detailed discussion about existing common features. The current study presents, a case series of 15 patients of rhino-orbital-cerebral mucormycosis (ROCM) including clinical data; common radiographic features like sinusitis, bony erosions, and soft tissue involvement also there were few uncommon features illustrated while evaluating the radiographic imaging. All patients underwent chair side and histopathological investigations. Appropriate treatment modalities were enrolled followed by rehabilitation of the defects after a thorough follow-up over an interval of 6 months. A thorough examination of the imaging findings is necessary since the aggressive nature of the infection can involve any parts of head and neck region illustrating few rare presentations involving uncommon sites. Radiologists must be aware of these unravelling radiographic features to know the precise extension of the infection.